Effectiveness of Tephrosia vogelii and Tephrosia candida Extracts against Common Bean Aphid (Aphis fabae) in Malawi - Chicco D. M. Kayange; Dalo Njera; Stephen P. Nyirenda; Louis Mwamlima (Advances in Agriculture)
Common beans (Phaseolus vulgaris) remain an important dietary protein source in Malawi. However, its production is highly hindered by insect pest and disease attack. The study aimed at evaluating the effectiveness of Tephrosia vogelii and Tephrosia candida extracts against bean aphid (Aphis fabae). The evaluation involved two botanical extracts at three different concentrations (0.5%, 2%, and 5% w/v) against bean aphid. Plant extracts (leaves) were air-dried and milled. Powders were then soaked in a 2-litre plastic bucket of cold water. Results indicated that there was significant difference (P<0.05) among treatments. The effectiveness of the treatments was based on reduction in aphid population per plant, pod length, and bean yield. Pod length and bean yield were higher in T. vogelii and Karate as compared to untreated and T. candida. There was a high mortality rate of aphid on the plots treated with T. vogelii compared to plots treated with T. candida at the same concentration. Though these two plant extracts were not as effective as the synthetic insecticide in reducing aphid population, they were considerably and significantly found to be effective; hence, its use by poor-resource farmers is recommended in the protection of bean against aphid.